Desenvolvimento de dispositivo para análise tribológica de ferramentas de corte para torno - Lima, Luiz Henrique Sartori (2015)
Through time, many were the technological advances in the field of machining inside the industry, with the development of new machines and types of cutting tools. However, these new types of tools are developed to obtain maximum performance in machines which are also new and, thus, suffer little from clearance fits and vibration. Nonetheless, such machines are financially impracticable for the vast majority of small businesses, where simpler machinery is still ubiquitous. For this reason, the problems mentioned above are apparent, and the utilization of newer types of tools becomes inappropriate. This is why it is necessary to search for improvements in this sector of the industry. Being so, this project aims to continue the study of improvements to duplex-treated high-speed steel tools. Therefore, a device for the evaluation of the performance of samples, in relation to wear, was developed. To accomplish this, fixation bases were designed for the piezoelectric platform as well as for the samples. A methodology was also elaborated for conducting trials, and it was validated through trials by using both the developed device and by microscope analysis (stereo and confocal).